2016
DOI: 10.1002/oby.21653
|View full text |Cite
|
Sign up to set email alerts
|

How Strongly Does Appetite Counter Weight Loss? Quantification of the Feedback Control of Human Energy Intake

Abstract: Objective To quantify the feedback control of energy intake in response to long-term covert manipulation of energy balance in free-living humans. Methods We used a validated mathematical method to calculate energy intake changes during a 52 week placebo-controlled trial in 153 patients treated with canagliflozin, a sodium glucose co-transporter inhibitor that increases urinary glucose excretion thereby resulting in weight loss without patients being directly aware of the energy deficit. We analyzed the relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(207 citation statements)
references
References 44 publications
(69 reference statements)
8
189
1
4
Order By: Relevance
“…However, this theory does not accord with the general experience of individuals when dieting. Furthermore, under the settling point model, we would not expect to see any compensatory changes in energy expenditure or intake to resist changes in energy balance -yet such changes are routinely observed (Norgan and Durnin, 1980;Leibel et al, 1995;Horton et al, 1995;Dulloo et al, 1997;Dulloo and Jacquet, 1998;Goldberg et al, 1998;Weyer et al, 2001;Galgani and Santos, 2016;Hall et al, 2011Hall et al, , 2012Johannsen et al, 2012;Polidori et al, 2016). A review of 32 controlled feeding studies in humans concluded that the responses were most consistent with the set-point rather than the settling point model (Hall and Guo, 2017).…”
Section: Settling Point Theorymentioning
confidence: 99%
“…However, this theory does not accord with the general experience of individuals when dieting. Furthermore, under the settling point model, we would not expect to see any compensatory changes in energy expenditure or intake to resist changes in energy balance -yet such changes are routinely observed (Norgan and Durnin, 1980;Leibel et al, 1995;Horton et al, 1995;Dulloo et al, 1997;Dulloo and Jacquet, 1998;Goldberg et al, 1998;Weyer et al, 2001;Galgani and Santos, 2016;Hall et al, 2011Hall et al, , 2012Johannsen et al, 2012;Polidori et al, 2016). A review of 32 controlled feeding studies in humans concluded that the responses were most consistent with the set-point rather than the settling point model (Hall and Guo, 2017).…”
Section: Settling Point Theorymentioning
confidence: 99%
“…These problems were recently addressed and the strength of the long-term energy intake feedback control circuit was quantified for the first time in humans. 88 …”
Section: Feedback Control Of Energy Intakementioning
confidence: 99%
“…88 The loss of glucose calories occurred without the subjects being directly aware of the calorie deficit and resulted in gradual weight loss. The subjects were found to progressively increase average energy intake by about 100 kcal/d per kilogram of lost weight – an effect more than 3-fold larger than the corresponding energy expenditure adaptations to weight loss.…”
Section: Feedback Control Of Energy Intakementioning
confidence: 99%
“…At the same time there will be a small decrease in energy expenditure associated with the loss of body weight. Together, all else being equal, these effects will cause weight settle (plateau) at a new lower level (11,12,13,14) . How much lower will depend on the extent of the initial reduction in energy intake achieved by use of LCS.…”
Section: Energy Balancing and The Potential Usefulness Of Consuming Smentioning
confidence: 99%